The "Best of Both Worlds": Building a community‐academic partnership for research with legal system‐impacted individuals. - Cohen, Talia R.; Reece, Karen; Hicks, Aaron; Mejchar, Deborah; Alonso, Carmen; Cooper, Anthony; Koenigs, Michael R.; Grupe, Daniel W. (American Journal of Community Psychology, 2025)
Equitable community‐academic research partnerships provide an innovative way to advance health outcomes among criminal legal system‐impacted individuals. The extant literature lacks accounts that detail the process for developing such partnerships, particularly in community‐based (rather than carceral) settings and with community organizations (rather than system actors). This First‐Person Account—co‐written by members of a research team consisting of academic researchers and community partners, including formerly incarcerated individuals—details opportunities and challenges that emerged through a year‐long pilot project intended to adapt a mental health intervention for correctional settings. The narrow focus of this project expanded dramatically over the course of the year as team members adapted to working together and realized the potential for the sustained impact of a long‐term collaboration. Key elements allowing for successful partnership development included (1) devoting time to building relationships in addition to "doing business"; (2) flexibility regarding the project aims and approach, which allowed for more equitable decision‐making; and (3) striving to understand and trust each other's respective expertise, whether based in academic training or lived experiences. Our experiences translate core principles of community‐based participatory research into concrete actions and practical examples of how to center the perspective of criminal legal system‐impacted individuals. Highlights: We built a community‐academic research partnership to advance mental health in the prison setting (99).Successful partnership formation depends on flexibility, shared decision‐making, and relationships (100).Credentialed expertise and lived expertise of incarceration are equally valuable for research (96).